RhoA-ROCK Signaling as a Therapeutic Target in Traumatic Brain Injury - Shalaka Mulherkar (Cells, 2020)
Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. TBIs, which range in severity from mild to severe, occur when a traumatic event, such as a fall, a traffic accident, or a blow, causes the brain to move rapidly within the skull, resulting in damage. Long-term consequences of TBI can include motor and cognitive deficits and emotional disturbances that result in a reduced quality of life and work productivity. Recovery from TBI can be challenging due to a lack of effective treatment options for repairing TBI-induced neural damage and alleviating functional impairments. Central nervous system (CNS) injury and disease are known to induce the activation of the small GTPase RhoA and its downstream effector Rho kinase (ROCK). Activation of this signaling pathway promotes cell death and the retraction and loss of neural processes and synapses, which mediate information flow and storage in the brain. Thus, inhibiting RhoA-ROCK signaling has emerged as a promising approach for treating CNS disorders. In this review, we discuss targeting the RhoA-ROCK pathway as a therapeutic strategy for treating TBI and summarize the recent advances in the development of RhoA-ROCK inhibitors.